2022
DOI: 10.1098/rsos.220716
|View full text |Cite
|
Sign up to set email alerts
|

The voice of few, the opinions of many: evidence of social biases in Twitter COVID-19 fake news sharing

Abstract: Online platforms play a relevant role in the creation and diffusion of false or misleading news. Concerningly, the COVID-19 pandemic is shaping a communication network which reflects the emergence of collective attention towards a topic that rapidly gained universal interest. Here, we characterize the dynamics of this network on Twitter, analysing how unreliable content distributes among its users. We find that a minority of accounts is responsible for the majority of the misinformation circulating online, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…For instance, we can use bow-tie structure to investigate potential distinctions between misinformation and scientific information dissemination. A recent paper [ 16 ] highlights that a minority of accounts are responsible for the majority of the misinformation circulating on Twitter, a pattern highly pertinent to our bow-tie structure analysis. Bow-tie structure may also help explain the phenomenon of infodemic in misinformation circulation, which describes the situation where exposure to an abundance of information undermines people’s ability to discern disinformation, thus facilitating its dissemination [ 17 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, we can use bow-tie structure to investigate potential distinctions between misinformation and scientific information dissemination. A recent paper [ 16 ] highlights that a minority of accounts are responsible for the majority of the misinformation circulating on Twitter, a pattern highly pertinent to our bow-tie structure analysis. Bow-tie structure may also help explain the phenomenon of infodemic in misinformation circulation, which describes the situation where exposure to an abundance of information undermines people’s ability to discern disinformation, thus facilitating its dissemination [ 17 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given the significant impact of online social media platforms as sources of information, a number of studies have emphasized their effect on vaccination views in public opinion [7][8][9][10][11][12]. Recent studies have highlighted the significance of the information 'creator-receiver' dynamics in online vaccination campaigns: some researchers have found that vaccination opponents tend to produce a higher volume of information than vaccination supporters [12][13][14][15]; several studies have observed that most (mis)information is created by a minority of users (which should not be assumed to be representative of a majority) and that information roles tend to remain relatively stable over time [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Social networks that are particular to a region can provide user behavior data that can inform early warning detection systems specific to that region; for example, using Baidu search data, Qin et al [ 56 ] were able to predict the number of new COVID-19 cases such as fever, coronavirus , and pneumonia . Their study, along with similar social media–based early warning detection efforts [ 37 - 40 ], shows potential for the creation of a more effective yet affordable model to forecast new cases.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, forecasting models have been created to track demand for ICU capacity planning in countries such as Chile [ 32 , 33 ], Brazil [ 34 ], Colombia [ 35 ], the United States [ 36 ], India [ 37 ], and China [ 38 ]. Previous studies have applied convergent cross-mapping (CCM) analysis to explore possible relationships involving antiepidemic measure–related tweets [ 39 ], the dynamics of misleading news on Twitter [ 40 ], and the identification of the global drivers of influenza [ 41 ]. However, to our knowledge, there are limited studies examining the potential of social media, particularly Twitter, to better understand hospital bed demand.…”
Section: Introductionmentioning
confidence: 99%
“…Fake news, in the form of misinformation and disinformation, has received much attention and scrutiny among scholars and policy makers in recent years. This is because the spread of fake news is considered as an information disorder (Castioni et al, 2022 ; Wang et al, 2019 ) that has social, political, and economic implications. Likewise, policy makers have been looking for the solutions using various strategies such as developing news verification and fake news detection tools (Tandoc et al, 2018 ), enforcing strict laws and regulations (Roozenbeek & van der Linden, 2019 ) and promoting digital literacy or fake news awareness in society to counter fake news spread (Torres et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%